MEMBANGUN ETIKA PENGGUNAAN TEKNOLOGI INFORMASI DAN PENTINGNYA MENJAGA DATA PRIBADI DI PANTI ASUHAN MUARA KASIH BUNDA: MEMBANGUN ETIKA PENGGUNAAN TEKNOLOGI INFORMASI DAN PENTINGNYA MENJAGA DATA PRIBADI DI PANTI ASUHAN MUARA KASIH BUNDA - Ronaldo, Muhammad Deva; Rumondang Tampubolon, Margareth; Zaki, Muhammad; Atra, Jhanu; Malik, Zainal Rahman; Zaliman, Iski (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2024)
This community service focuses on the importance of instilling ethical values and data security awareness in children to prevent potential risks related to data misuse, especially among orphanage children. The service is conducted through socialization using qualitative methods, participatory approaches, and experiential learning theories to actively engage children in learning about the ethics of technology use and data security. The methodology includes interactive sessions such as material presentations and Q&A sessions to enhance understanding and internalization of ethical values. The results show that children actively participated in the sessions, increasing their awareness of the importance of protecting personal data and applying ethical principles in everyday technology use. Factors such as privacy awareness and safe and responsible technology use play a crucial role in creating a safe and ethical environment for information technology use in the orphanage. This service demonstrates the effectiveness of experiential learning and outreach activities in promoting ethical technology use and data security awareness among children. This activity can serve as an effective model for other community service programs in the field of information technology ethics education for the younger generation.